Information management and social media for student engagement in universities - Santos Barbosa, Everaldo Henrique dos [UNESP]; Bassan de Moraes, Cassia Regina [UNESP] (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2022)
The data and information present in the media can be processed, interpreted and analyzed, identifying metrics that demonstrate the level of user engagement. They can also promote the engagement of current and future students in higher education institutions. So, the research question: what content strategies contribute to social media engagement of current and future students? The overall objective was to identify the most appropriate content strategies for using social media to engage students. The specific objectives are to identify which type of content on social media attracts more attention from the public and investigate measures that allow verifying information on student behavior. This research is did characterize as exploratory and quantitative-descriptive in nature, using the Case Study method by Yin (2010) carried out in a higher education institution in the state of Sao Paulo, Brazil. The research subjects involve 109 students and 2 employees responsible for social media. A guiding framework was did built from the interrelation of the concepts of information management and social media, generating indicators for the use of social media. The institution's social profile on Facebook has 4932 users and 246 publications for a period of one month. Signs of user engagement were did observe and photo-type publications were found to be the ones with the most involvement. The entrance exam period represents the greatest flow of publications. In addition, 82.6% of Internet users said they feel closer to the institution.
Keywords: Brazil; Information Management; Media engagement; Social media; Social networks